Co-design and assessment of mitigation practices in rice production systems: A case study in northern Vietnam. (November 2018) - Tariq, Azeem; de Neergaard, Andreas; Jensen, Lars Stoumann; Sander, Bjoern Ole; Trinh, Mai Van; Vu, Quynh Duong; Wassmann, Reiner; de Tourdonnet, Stephane
Abstract: Rice production systems are an important source of agricultural greenhouse gas (GHG) emissions. Mitigation techniques, such as alternate wetting and drying, have been developed but have often not taken into consideration the constraints imposed by the practices and preferences of farmers. Since GHG mitigation benefits are not obvious at smallholder farm level, it is essential to design site-specific mitigation technologies with the participation of local stakeholders. The purpose of the present study was to adapt a participatory approach to designing and assessing mitigation practices for the dissemination of climate-friendly rice production systems. To improve the hybridization of scientific and local knowledge, a participatory five-step approach to prototyping was applied: (i) diagnosis based on a literature review and survey of stakeholders, (ii) design of mitigation practices based on laboratory trial and local knowledge (that of farmers, agricultural advisors and regional stakeholders), (iii) testing in growth chambers, (iv) testing in farmers' fields and (v) dissemination and assessment. The study was conducted in An Luong village, Red River Delta, northern Vietnam. In the study area, rice residue burning is restricted and farmers have to incorporate residue into the soil. Current water management practices, i.e. conventional continuous flooding and adopted midseason drainage, are not enough to reduce GHG emissions from added residues. Two new water management practices (pre-planting plus midseason drainage and early plus midseason drainage) were designed in participation with local stakeholders, and subsequently tested in the laboratory and in the field with the participation of local farmers. Future mitigation practices were assessed based on the yield, GHG emissions reduction and feedbacks of local stakeholders. Early plus midseason drainage proved to be an effective and feasible mitigation option for rice production in the area. Here we show that participation of local stakeholders in co-designing process help to identify the feasible GHG mitigation options, further it facilitates smallholder rice farmers to implement mitigation practices in their fields. Graphical abstract: Highlights: CH4 emissions from rice fields is a significant source of GHG emissions in Vietnam. A participatory method was adapted to co-design the mitigation practices. Smallholders have limited resources for sustainable management of crop residues. Pilot trials on farmers' fields increase their confidence to embrace new practices. Multistakeholder analyses are required for developing feasible mitigation solution.